(untitled) (Academia Journal of Medicine, 2019)
Background: The incidence of IPF was estimated at 10.7 cases per 100,000 per year for men and 7.4 cases per 100,000 per year for women in a population-based study from the county of Bernalillo, New Mexico. A study from the United Kingdom reported an overall incidence rate of only 4.6 per 100,000 person-years, but estimated that the incidence of IPF increased by 11% annually between 1991 and 2003. This increase was not felt to be attributable to the aging of the population or increased ascertainment of milder cases. Subjects and Methods: This was an observational prospective study carried out in the Department of Pulmonary Medicine, Medical College. The study included 35 patients diagnosed with IPF during the two year study period. Results: Dyspnea was the most common symptom at presentation, being present in 35 (100 %) of the patients. Cough with or without expectoration was the next most common symptom, being present in 33 (94.2 %) of the patients. Other symptoms were chest pain, fever and weight loss, and joint pains. Conclusion: Clinical prediction models are used in many areas of medicine to provide accurate prognostic information and staging of disease; such a prediction model would be useful in IPF.